2021
DOI: 10.3390/ani11071862
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Microbial Profiles of Colonic Digesta between Ningxiang Pig and Large White Pig

Abstract: Sixteen 35-day-old piglets, including eight Large White (LW) piglets (a lean-type pig breed) and eight Ningxiang (NX) piglets (a fatty-type Chinese Indigenous pig breed), were fed the same diet for 105 days. NX pigs had higher intramuscular fat content than LW pigs (p < 0.05). According to 16S rRNA gene sequencing, the relative abundances of the genera Ruminococcaceae_NK4A214_group, Parabacteroides, Christensenellaaceae_R-7_group and Ruminiclostridium were higher, whereas the abundances of Prevotellaceae_NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The number of pigs in the world is estimated to be approximately 1 billion. Intestinal microbes can regulate the growth characteristics and health status of the host, such as fat deposition traits ( Lei et al, 2021 ), chronic diseases (cancer and metabolic disorders) ( Coleman et al, 2018 ; Just et al, 2018 ; Zitvogel et al, 2018 ), and disease resistance (resistance to intestinal infection) ( Kumar et al, 2018 ). The Tibetan pig is a unique and valuable pig breed from the Tibetan Plateau that shows strong fat deposition ability, strong disease resistance, adaptability to high altitude hypoxia, and resistance to the cold and rough feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The number of pigs in the world is estimated to be approximately 1 billion. Intestinal microbes can regulate the growth characteristics and health status of the host, such as fat deposition traits ( Lei et al, 2021 ), chronic diseases (cancer and metabolic disorders) ( Coleman et al, 2018 ; Just et al, 2018 ; Zitvogel et al, 2018 ), and disease resistance (resistance to intestinal infection) ( Kumar et al, 2018 ). The Tibetan pig is a unique and valuable pig breed from the Tibetan Plateau that shows strong fat deposition ability, strong disease resistance, adaptability to high altitude hypoxia, and resistance to the cold and rough feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Bama pigs serve as ideal models for biomedical research, which are exhibited by a high intramuscular fat content ( 17 ). In addition, NingX pigs, a well-known Chinese indigenous fatty-type breed, have gained more diverse bacterial communities ( 18 ). Although the performance, appearance, and original geographic location of these breeds are variant, the microbiota does contribute to shaping their anti-stress ability compared to commercial hybrid piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion frequency was different between two types of pig and dominant for LEPROT -SINE-RIP in Chinese native breeds and LEPR -SINE-RIP in commercial pigs. Several studies have indicated that compared to commercial pigs, native pigs showed a slower growth rate, thicker backfat, and low lean percentage [ 39 , 40 , 41 , 42 , 43 ]. Natural selection and genetic drift are also powerful forces shaping the distribution and accumulation of retrotransposons [ 44 ].…”
Section: Discussionmentioning
confidence: 99%